Pathophysiological analysis of the progression of hepatic lesions in STAM mice - Saito, T; Muramatsu, M; Ishii, Y; Saigo, Y; Konuma, T; Toriniwa, Y; Miyajima, K; Ohta, T (Physiological research, 2017)
Nonalcoholic steatohepatitis (NASH) is a current health issue since the disease often leads to hepatocellular carcinoma; however, the pathogenesis of the disease has still not been fully elucidated. In this study, we investigated the pathophysiological changes observed in hepatic lesions in STAM mice, a novel NASH model. STAM mice, high fat-diet (HFD) fed mice, and streptozotocin (STZ) treated mice were prepared, and changes over time, such as biological parameters, mRNA expression, and histopathological findings, were evaluated once animal reached 5, 7, and 10 weeks of age. STZ mice presented with hyperglycemia and an increase in oxidative stress in immunohistochemical analyses of Hexanoyl-lysine: HEL from 5 weeks, with fibrosis in the liver also being observed from 5 weeks. HFD mice presented with hyperinsulinemia from 7 weeks and the slight hepatosteatosis was observed at 5 weeks, with changes significantly increasing until 10 weeks. STAM mice at 10 weeks showed significant hepatic changes, including hepatosteatosis, hypertrophic hepatocytes, and fibrosis, indicating pathological changes associated with NASH. These results suggested that the increase in oxidative stress with hyperglycemia triggered hepatic lesions in STAM mice, and insulin resistance promoted lesion formation with hepatic lipid accumulation. STAM mice may be a useful model for elucidating the pathogenesis of NASH with diabetes.
Keywords: Liver; játra; Disease Progression; krevní glukóza; těhotenství; progrese nemoci; Non-alcoholic Fatty Liver Disease; myši inbrední C57BL; mužské pohlaví; nealkoholová steatóza jater; Mice; Diet, High-Fat; dieta s vysokým obsahem tuků; Body Weight; Organ Size; velikost orgánu; Blood Glucose; ženské pohlaví; zvířata; Pregnancy; tělesná hmotnost; myši; Female; Mice, Inbred C57BL; Male; Animals